E-commerce strategy and global EC / Fatanah Jislan ... [et al.] - Jislan, Fatanah; Md Sabri, Sabiroh; Yusoff, Sarah; Sa'dan, Siti 'Aisyah; Wan Mohamad, Siti Hajar; Omar Ali, Siti Rapidah; Ibrahim, Ismi Safia Adila (2013)
The emergence of Internet and technologies has encouraged rapidly the development and growth of e-commerce locally and internationally which constantly changes the area of business management. E- commerce offers great opportunity for all businesses to improve and maintain its competitiveness. In order to understand e-commerce, it is important to implement the various strategies that would enable the businesses to operate smoothly as well as meeting customer's satisfaction and their trust. In order to do so, E-commerce comes with various strategies which are initiation, formulation, implementation, and assessment. Apart from that, the businesses should also address the global EC issues related to e-commerce strategies as to ensure the successful of its transaction and ability to penetrate larger markets. The global EC issues focused on cultural, culture and language translation, administrative, geography and localization as well as economics.